Pelatihan Penulisan Ilmiah Berbasis AI: Meningkatkan Kompetensi Penelitian Mahasiswa Pascasarjana Universitas Pakuan - Santoso, Teguh Iman (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
The use of Artificial Intelligence (AI) technology in the process of writing scientific articles has the potential to improve the research competence of postgraduate students, both in terms of efficiency, quality, and development of ethical perspectives. The hybrid workshop training themed "Improving Research Competence through Writing Scientific Articles with the Assistance of AI Technology" at the Postgraduate School of Pakuan University was attended by 178 participants from various study programs. This training focused on the use of AI-based tools, such as Jenny AI and Quillbot AI for drafting and improving text coherence, Avidnote AI in literature management and annotation, and Scite AI for evaluating reference credibility. The evaluation showed that the majority of participants rated the material as very relevant (55.1%) and relevant (38.8%) to their research needs, especially in the technical aspects of utilizing AI tools, ethics of use (eg prevention of plagiarism), and understanding scientific integrity. Although in general the material and committee services were considered clear, participants indicated the need for more in-depth follow-up training, including onsite sessions that focused on strengthening practical skills and managing academic writing ethics. Thus, this training contributes to improving students' research competence through the integration of AI technology in scientific writing. Future recommendations include the development of more structured advanced training modules, ongoing mentoring, and the development of materials on ethical management of AI use, so that the impact of training can be more sustainable and comprehensive.ABSTRAKPenggunaan teknologi Kecerdasan Buatan (Artificial Intelligence, AI) dalam proses penulisan artikel ilmiah berpotensi meningkatkan kompetensi penelitian mahasiswa pascasarjana, baik dari segi efisiensi, kualitas, maupun pengembangan perspektif etis. Pelatihan hybrid workshop bertema "Peningkatan Kompetensi Penelitian melalui Penulisan Artikel Ilmiah dengan Bantuan Teknologi AI" di Sekolah Pascasarjana Universitas Pakuan diikuti oleh 178 peserta dari berbagai program studi. Pelatihan ini berfokus pada pemanfaatan alat berbasis AI, seperti Jenny AI dan Quillbot AI untuk penyusunan draf dan peningkatan koherensi teks, Avidnote AI dalam manajemen dan anotasi literatur, serta Scite AI untuk evaluasi kredibilitas referensi. Evaluasi menunjukkan mayoritas peserta menilai materi sebagai sangat relevan (55,1%) dan relevan (38,8%) dengan kebutuhan penelitian mereka, khususnya dalam aspek teknis pemanfaatan alat AI, etika penggunaan (misalnya pencegahan plagiarisme), serta pemahaman integritas ilmiah. Meskipun secara umum materi dan pelayanan panitia dinilai jelas, peserta mengindikasikan perlunya pelatihan lanjutan yang lebih mendalam, termasuk sesi onsite yang berfokus pada penguatan keterampilan praktis dan pengelolaan etika penulisan akademik. Dengan demikian, pelatihan ini berkontribusi pada peningkatan kompetensi penelitian mahasiswa melalui integrasi teknologi AI dalam penulisan ilmiah. Rekomendasi ke depan mencakup penyusunan modul pelatihan lanjutan yang lebih terstruktur, pendampingan berkelanjutan, serta pengembangan materi tentang pengelolaan etis penggunaan AI, sehingga dampak pelatihan dapat lebih berkelanjutan dan komprehensif.